Efficacy and safety of 12-hour versus 24-hour magnesium sulfate in management of patients with pre-eclampsia and eclampsia: a systematic review and meta-analysis - Rahma Sameh Shaheen; Rahma Abdelaziz Ismail; Esraa Y. Salama; Sally Median Korini; Ahmed Saad Elsaeidy (BMC Women's Health, 2024)
Abstract Introduction Magnesium sulfate is the most utilized anticonvulsant for treating patients with eclampsia and pre-eclampsia. The purpose of this study is to determine whether the 12-h regimen of magnesium sulfate outweighs the 24-h regimen in both efficacy and safety in the management of patients with mild or severe pre-eclampsia and eclampsia. Methods We searched six electronic databases: PubMed, Scopus, Web of Science, Cochrane Library, Ovid, and Google Scholar. This search was conducted to yield any studies that were published until 15 January 2023. We did the statistical analysis plan by Review Manager Software version 5.4. Results We included 13 randomized control trials with 2813 patients in this systematic review. Our meta-analysis revealed that there were no statistically significant differences between the 12-h regimen of the magnesium sulfate group and the 24-h regimen of the magnesium sulfate group in our outcome of interest: occurrence of seizure (RD: -0.00, 95% CI [-0.01, 0.00], P = 0.56), diminished deep tendon reflexes (RD: -0.00, 95% CI [-0.01, 0.01], P = 0.80), respiratory depression (RD: -0.00, 95% CI [-0.02, 0.01], P = 0.57), and pulmonary edema (RD: -0.00, 95% CI [-0.01, 0.01], P = 0.85). Conclusion Our study showed no statistically significant difference in effectiveness and toxicity risk between the 12-h and 24-h regimens.